1989
DOI: 10.1002/jor.1100070404
|View full text |Cite
|
Sign up to set email alerts
|

Use of patellar tendon autograft for anterior cruciate ligament reconstruction in the rabbit: A long‐term histologic and biomechanical study

Abstract: To assess the degree of success of anterior cruciate ligament (ACL) replacement using the patellar tendon (PT) autograft, 29 New Zealand white rabbits underwent ACL reconstruction using a medial one-third PT autograft. The femur-ligament-tibia complexes were evaluated at 0, 6, 30, and 52 weeks postoperatively for gross and histologic appearances and tensile load to failure properties. Grossly, the autografts did not resemble the control ACLs. Histologically, the autografts progressed from being hypercellular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(99 citation statements)
references
References 31 publications
7
89
0
3
Order By: Relevance
“…Standardized instrumented knee laxity tests have been successfully performed on animal knees in vitro: rabbits (e.g. Ballock et a!., 1989), dogs (e.g. Woo et ai., 1987a), sheep (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized instrumented knee laxity tests have been successfully performed on animal knees in vitro: rabbits (e.g. Ballock et a!., 1989), dogs (e.g. Woo et ai., 1987a), sheep (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Oster et ai, 1992). Two different tests are com mon, the anterior-posterior test to examine the function of the cruciate ligaments (Amendola and Fowler, 1992;Ballock et a 1989;Oster et alt 1992) and the varus-valgus test to determine the function of the collateral ligaments (Oster et a!., 1992;Woo et ul, 1987a).…”
Section: Introductionmentioning
confidence: 99%
“…An overall concern during this phase is evidence that the autograft itself is reaching its weakest point structurally during the 6 to 8 week time frame postoperatively [16]. Additional evidence states that the actual graft may only reach between 11 and 50% failure loads of the native ACL at the 1-year point [17]. It is theorized that controlled loading will enhance ligament and tendon healing, while excessive stress loading to an ACL graft may cause graft elongation leading to excessive unwanted anterior-posterior laxity [44,82,83].…”
Section: Phase Iii: Postoperative 6 Weeks-3 Monthsmentioning
confidence: 99%
“…This usually starts at approximately weeks 6-8 at which time animal studies have shown that the graft is at its weakest point in the post reconstruction process [16]. Some studies indicate that the graft may only reach failure loads of 11 to 50% at 1 year post-operative [17]. This process continues with cellular proliferation in which cells other than the native graft tissue may inhabit the graft.…”
Section: Introductionmentioning
confidence: 99%
“…These changes can be divided into four stages: (i) avascular necrosis, (ii) revascularization, (iii) cellular proliferation, and (iv) remodeling . In the overall process, mechanical deterioration of the grafted tendon is observed (Ballock et al, 1989). However, the mechanism of the mechanical deterioration of the grafted tendon has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%